Wewenang Kepolisian dalam Melakukan Penyidikan terhadap Kasus Pencurian Motor di Polsek Kelapa Lima - Venti Jayantri Uly; Simplexius Asa; A. Resopijani (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
Motorcycle theft crimes can occur anywhere. Not only in big cities, but also in small cities, especially Kupang. Various efforts have been tried to reduce crime, but it still occurs frequently but with lower intensity. The incomplete handling of motorcycle theft cases by the police will actually have a negative impact, including weak law enforcement, public apathy towards the law, unrest among members of the motorcycle owner community, increased opportunities for similar crimes, and the worsening image of the police in society. The method used in this study is empirical research with interview techniques and document studies, then analyzed and compiled systematically. The results of the study indicate that the Police Authority in Handling Motorcycle Theft Cases and Constraints in Handling Motorcycle Theft Cases are the Community is less responsive in reporting, Difficulty finding evidence and High mobility of perpetrators Efforts to reduce motorcycle theft crimes that occur are by increasing the readiness of police officers in following up on reports that there have been crimes of motor vehicle theft which must be supported by information from the community, so that they are faster and more in revealing motor vehicle theft crimes And it must be further improved to make appeals and socialization to the community about the capture of motor vehicle theft and avoid the community to increase vigilance.